2017
DOI: 10.1371/journal.pgen.1006865
|View full text |Cite|
|
Sign up to set email alerts
|

The WAGR syndrome gene PRRG4 is a functional homologue of the commissureless axon guidance gene

Abstract: WAGR syndrome is characterized by Wilm’s tumor, aniridia, genitourinary abnormalities and intellectual disabilities. WAGR is caused by a chromosomal deletion that includes the PAX6, WT1 and PRRG4 genes. PRRG4 is proposed to contribute to the autistic symptoms of WAGR syndrome, but the molecular function of PRRG4 genes remains unknown. The Drosophila commissureless (comm) gene encodes a short transmembrane protein characterized by PY motifs, features that are shared by the PRRG4 protein. Comm intercepts the Rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 80 publications
1
35
0
Order By: Relevance
“…However, a proline rich and Gla domain protein, PRRG4, containing the L/PPxY motifs found in Comm was recently shown to affect a hRobo1 expression phenotype in flies (Justice et al 2017). In addition, PRRG4 is able to re-localise hRobo1 from cell surfaces, which taken together strongly suggest it's a functional homologue of Comm (Justice et al 2017). The role of endocytosis in Slit-Robo signalling is further supported by Drosophila genetic experiments and complementary in vitro data (Chance and Bashaw 2015).…”
Section: Robo Signalling Mechanismmentioning
confidence: 90%
See 2 more Smart Citations
“…However, a proline rich and Gla domain protein, PRRG4, containing the L/PPxY motifs found in Comm was recently shown to affect a hRobo1 expression phenotype in flies (Justice et al 2017). In addition, PRRG4 is able to re-localise hRobo1 from cell surfaces, which taken together strongly suggest it's a functional homologue of Comm (Justice et al 2017). The role of endocytosis in Slit-Robo signalling is further supported by Drosophila genetic experiments and complementary in vitro data (Chance and Bashaw 2015).…”
Section: Robo Signalling Mechanismmentioning
confidence: 90%
“…While Slit-Robo signalling is conserved in bilateral species, and endocytosis was shown to be important for Slit2 mediated collapse of Xenopus retinal growth cones (Piper et al 2006), no Comm proteins were identified in vertebrates. However, a proline rich and Gla domain protein, PRRG4, containing the L/PPxY motifs found in Comm was recently shown to affect a hRobo1 expression phenotype in flies (Justice et al 2017). In addition, PRRG4 is able to re-localise hRobo1 from cell surfaces, which taken together strongly suggest it's a functional homologue of Comm (Justice et al 2017).…”
Section: Robo Signalling Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity or severe hyperphagia has also been described in a subgroup of these patients, in which case the condition is often called WAGRO . Secondary features often seen in WAGR patients are renal problems, cardiopulmonary defects and behavioral difficulties like autism . Due to the specific combination of manifestations, the differential diagnosis of WAGR is very limited.…”
Section: Wilms Tumor Aniridia Genitourinary Malformations and Mentamentioning
confidence: 99%
“…[156][157][158][159][160][161][162] Secondary features often seen in WAGR patients are renal problems, cardiopulmonary defects and behavioral difficulties like autism. 160,163 Due to the specific combination of manifestations, the differential diagnosis of WAGR is very limited.…”
Section: Bardet-biedl Syndromementioning
confidence: 99%